A translation and commentary of Ibn `Ābidīn’s Al-`Ilm Al-Ẓāhir Fī Naf`I Al-Nasab Al-Ṭāhir (Evident knowledge on the benefit of pure lineage) - Abdul Razak al-Aidrus, Mohamed Ajmal; Ali, Mohammed Farid (ISTAC, 2014)
This article consists of the translation of Ibnu Abidin’s views on the position of the family of the Prophet Muhammad by virtue of their blood ties to him here and the Hereafter. The work also covers critically the opinions of both sides of the argument as to their standing. Ibnu Abidin himself was a “Sayyid” and in his work extols his position as one. Nevertheless, his article provides a number of hadiths that can help provide a balanced look at the claims of a special position of the family of the Prophet as defined by history, tradition and culture.